Pemanfaatan Aplikasi Point of Sales Untuk Prediksi Stock Barang Dengan Metode Fuzzy Tsukamoto - Ardaneswari, Awanda; Sediyono, Eko (Computatio : Journal of Computer Science and Information Systems, 2020)
Procurement of goods and completeness of goods becomes a matter that greatly determines therunning of the business process of a business. There needs to be an increase in goods management strategies so that no items accumulate in the warehouse or supply of existing goods cannot balance with demands of goods. The user of the Point of Sales application is an effort to improve management of goods and employees. Unfortunately the use of applications is not optimal makes the business stagnant. Furthermore, this study focuses on the utilization of report data from application Point of Sales (POS) to produce predictions of goods stock using the Fuzzy Tsukamoto method. It is expected that the results of this prediction will allow business owners to improve the quality of service from the procurement side of goods that have an impact on customer satisfaction and also reduce the level of business losses AbstrakPengadaan barang dan kelengkapan barang menjadi hal yang sangat menetukan berjalannya proses bisnis suatu usaha. Perlu adanya peningkatan strategi manajemen barang sehingga tidak ada barang yang menumpuk di gudang atau sebaliknya barang yang ada tidak dapat memenuhi permintaan pasar. Penggunaan aplikasi Point Of Sales menjadi salah satu upaya peningkatan manajemen barang serta karyawan. Sayangnya pemanfaatan aplikasi yang kurang maksimal membuat usaha menjadi stagnan. Lebih jauh, pada penelitian ini memfokuskan pada pemanfaatan data laporan dari aplikasi Point of Sales (POS) untuk menghasilkan prediksi stock barang dengan metode Fuzzy Tsukamoto. Hasil prediksi ini memungkinkan pemilik usaha untuk lebih meningkatkan kualitas pelayanan dari sisi pengadaan barang yang berdampak pada kepuasan pelanggan dan juga mengurangi tingkat kerugian usaha.